Characteristics of a paste explosive (EPX-P20) used in explosive bolts for spacecraft's applications. (September 2019) - Elbeih, Ahmed; Abdelhafiz, Mahmoud; Hussein, Ahmed K.; Wafy, Tamer Z.; Elshenawy, Tamer; Baraka, Ahmad; Elsayed, Mohamed A.; Gobara, Mohamed
Abstract: An explosive charge, located within a machined cavity in a bolt, provides the energetic stimulus required for cleanly bolt fracture. The shock wave produced fom the explosion causes tensile fracture along the bolt itself with minumum fragmentation and helps to control the separation process of the satellite from its rocket. In this study, EPX-P20 is a paste explosive in the research stage. EPX-P20 is based on PETN (pentaerythritol tetranitrate) bonded by polydimethyl-siloxane binder matrix. A computerizing mixer plastograph was used for the production of EPX-P20. The internal energy of combustion was measured and used to determine the enthalpy of formation. Sensitivity against both friction and impact stimuli were determined. The detonation properties were calculated theoretically using the EXPLO 5 soft code, while the detonation velocity was determined experimentally. For comparison, several commercial available explosives such as; Sprängdeg m/46, Formex P1, Semtex 10 and EPX-1 were investigated. It was proven that EPX-P20 possesses the lowest velocity of detonation while maintaining its very low sensitivity. Interesting inversely proportion relationship amongst the measured internal energy of combustion and the calculated heat of detonation was observed. The produced paste explosive might be used in explosive bolt for space craft's applications.